Hubungan antara Lingkungan Belajar dengan Pendekatan Belajar Mahasiswa Tahun Pertama Fakultas Kedokteran Universitas Lampung - Echa Putri Anjani; Merry Indah Sari; Ety Apriliana (Medula, 2020)
The learning environment in medical education cast of physical, non-physical/social context in which students study. The learning environment creates an atmosphere of learning that influences student behaviors and efforts that are visible from the way they choose a learning approach that ultimately affects learning outcomes. The learning approach consists of a deep approach and a surface approach. The study aim to find the relationship between the perception of learning environment and learning approach among first year student at the Medical Faculty Lampung University. This is a cross sectional study with sample of 214 first year medical students. Data were collected using Dundee Ready Educational Environment Measure (DREEM) and Revised Two-Factor Study Process Questionnaire (R-SPQ-2F). There are 87 students (40,7%) have excellent perception to learning environment and 127 students (59,3%) have good perception. There were 202 students (94.4%) using deep approach and 12 students (5.6%) using surface approach. Students have excellent perceptions of the learning environment with an deep approach of 84 students (96.6%) and using a surface approach of 3 students (3.4%). Students who have a good perception of the learning environment with deep approach of 118 students (92.9%) and using the surface approach of 9 students (7.1%). The data was statistically tested using Fisher exact test and p value is 0,368 (>0,05). The result there is no significant relationship between the perception of learning environment and learning approach among first year student at the Medical Faculty Lampung University.